Small size gold nanoparticles enhance apoptosis-induced by cold atmospheric plasma via depletion of intracellular GSH and modification of oxidative stress - Jawaid, Paras; Rehman, Mati Ur; Zhao, Qing-Li; Misawa, Masaki; Ishikawa, Kenji; Hori, Masaru; Shimizu, Tadamichi; Saitoh, Jun-ichi; Noguchi, Kyo; Kondo, Takashi (Cell death discovery, 2020)
Gold nanoparticles (Au-NPs) have attracted attention as a promising sensitizer owing to their high atomic number (Z), and because they are considered fully multifunctional, they are preferred over other metal nanoparticles. Cold atmospheric plasma (CAP) has also recently gained attention, especially for cancer treatment, by inducing apoptosis through the formation of reactive oxygen species (ROS). In this study, the activity of different sized Au-NPs with helium-based CAP (He-CAP) was analyzed, and the underlying mechanism was investigated. Treating cells with only small Au-NPs (2 nm) significantly enhanced He-CAP-induced apoptosis. In comparison, 40 nm and 100 nm Au-NPs failed to enhance cell death. Mechanistically, the synergistic enhancement was due to 2 nm Au-NPs-induced decrease in intracellular glutathione, which led to the generation of intracellular ROS. He-CAP markedly induced ROS generation in an aqueous medium; however, treatment with He-CAP alone did not induce intracellular ROS formation. In contrast, the combined treatment significantly enhanced the intracellular formation of superoxide (O 2 • − ) and hydroxyl radical ( • OH). These findings indicate the potential therapeutic use of Au-NPs in combination with CAP and further clarify the role of Au-NPs in He-CAP-aided therapies.